Microwave induced jet boiling investigated via voltammetry at ring-disk microelectrodes. - Ghanem, M; Thompson, M; Compton, R; Coles, B; Harvey, S; Parker, K; O'Hare, D; Marken, F (2006)
High intensity microwave radiation is (self-)focused at metal electrodes immersed in aqueous electrolyte solutions to generate highly localized superheating and convection effects. It is shown that, for an electrode pointing downward, low intensity microwave radiation causes density driven convective flow (upward), which at the onset of boiling abruptly switches to a fast jet of liquid moving away from the electrode surface (downward). This "jet-boiling" phenomenon allows extremely high rates of mass transport and mixing to be realized at the electrode surface. Cyclic voltammograms obtained at electrodes placed into a microwave field show very strong mass transport enhancement effects. Cyclic voltammograms recorded at a Pt/Pt ring-disk electrode system (r(1) = 25 microm, r(2) = 32 microm, r(3) = 32.4 microm) in the presence of microwave radiation are employed to further explore mass transport effects under microwave conditions. Mass transport coefficients, collection efficiencies, and temperatures are determined as a function of microwave intensity.